Advertising: A Case for Intersemiotic Translation - Torresi, Ira (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractIn the world of the printed page, pictures and graphic layout are generally taken to be mere complements or exemplifications of the verbal part of the text. This is not only against the principles of semiotics, it is against the very rules of communication, as the text is not perceived by the reader as a sum of different dimensions (i.e., verbal, visual, tactile, etc.) but as a whole where all components are connected and interdependent. Thus, splitting a text into its several dimensions is a completely artificial procedure that should be carried out for analytical purposes only, since all components of a text, as well as their interplay and the interplay of the text with its context and co-text, contribute to the construction of meaning. This cannot be ignored by translators and should be made clear to any client who may think that the act of translation is by definition limited to the verbal dimension, and may go as far as submitting texts for translation without providing briefs about the visual elements they will be “complemented” with, or the graphic conventions that will be adopted in the final version. The translation – or localization – of advertisements is a case in point. The visual component plays a prominent role in most forms of advertising, particularly so in magazine ads; developing the pictorial and graphic aspects of a campaign, however these might appear “casual,” is a time-consuming and expensive process. If the translator (or localizer) is responsible for the text resulting from his/her work, then, he/she cannot ignore its visual dimension, and should be prepared to suggest modifications not only to the verbal part of the text, but also to its many other dimensions, in a holistic, intersemiotic perspective. Real-life examples, not only from advertising but also from editorial translation, will be provided to support this argument.